2023
DOI: 10.1017/s0021932022000517
|View full text |Cite
|
Sign up to set email alerts
|

Parental background and daughters’ and sons’ educational outcomes – application of the Trivers-Willard hypothesis

Abstract: This study uses Trivers-Willard hypothesis to explain the differences in daughters’ and sons’ educational outcomes by parental background. According to the Trivers-Willard hypothesis (TWH), parental support and investments for sons and daughters display an asymmetrical relationship according to parental status because of the different reproductive advantage of the sexes. It predicts that high-status parents support sons more than daughters, and low-status parents support daughters more than sons. In modern soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In addition to socioeconomic background, studies have shown that the importance of parents' support for learning is central, e.g., [10,82,83]. The support, attitudes, and influences given by parents are reflected in the child.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to socioeconomic background, studies have shown that the importance of parents' support for learning is central, e.g., [10,82,83]. The support, attitudes, and influences given by parents are reflected in the child.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The difference in competence between the extreme groups who received parental support corresponded to two years of studies. Educated and high-income parents invest especially in boys' education and guide them more strongly to go to general upper secondary school [83].…”
Section: Environmental Factorsmentioning
confidence: 99%